Chronic kidney failure mineral bone disorder leads to a permanent loss of hematopoietic stem cells through dysfunction of the stem cell niche. Issue 1 (December 2018) - Aleksinskaya, Marina; Monge, Matthieu; Siebelt, Michiel; Slot, Edith; Koekkoek, Karin; Bruin, Ruben; Massy, Ziad; Weinans, Harrie; Rabelink, Ton; Fibbe, Willem; Zonneveld, Anton; Pel, Melissa
Abstract In chronic kidney disease (CKD), endothelial injury, is associated with disease progression and an increased risk for cardiovascular complications. Circulating cells with vascular reparative functions are hematopoietic and also reduced in CKD. To explore the mechanistic basis behind these observations, we have investigated hematopoietic stem cell (HSC) homeostasis in a mouse model for non-progressive CKD-mineral and bone disorder with experimentally induced chronic renal failure (CRF). In mice subjected to 12 weeks of CRF, bone marrow HSC frequencies were decreased and transplantation of bone marrow cells from CRF donors showed a decrease in long-term HSC repopulation compared to controls. This loss was directly associated with a CRF-induced defect in the HSC niche affecting the cell cycle status of HSC and could not be restored by the PTH-reducing agent cinacalcet. In CRF, frequencies of quiescent (G0) HSC were decreased coinciding with an increase in hematopoietic progenitor cells (HPC) in the S-and G2-phases of cell cycle. Moreover, in CRF mice, HSC-niche supporting macrophages were decreased compared to controls concomitant to impaired B lymphopoiesis. Our data point to a permanent loss of HSC and may provide insight into the root cause of the loss of homeostatic potential in CKD.